BENTUK PARTISIPASI MASYARAKAT DALAM KEGIATAN EKOWISATA DI OBJEK WISATA PANTAI LINTUI NEGERI KOBI KECAMATAN SERAM UTARA TIMUR KOBI KABUPATEN MALUKU TENGAH - Laila, Nur; Lelloltery, Henderina; Iskar, Iskar (Lambung Mangkurat University-Indonesia, 2025)
This research uses qualitative analysis methods, research procedures which produce descriptive data in the form of written and spoken words from people and observed behavior. The method used is a survey method where data is obtained by interviewing or filling in a list of questions, direct observation (observation) and literature study. The research results show that community participation can be seen in the form of incentive, interactive and initiative participation at OWA Lintui Beach.